Photoionisaton of pure and doped helium nanodroplets - Mudrich, M.; Stienkemeier, F. (International reviews in physical chemistry, 2014)
Helium nanodroplets, commonly regarded as the 'nearly ideal spectroscopic matrix', are being actively studied for more than two decades now. While they mostly serve as cold, weakly perturbing and transparent medium for high-resolution spectroscopy of embedded molecules, their intrinsic quantum properties such as microscopic superfluidity still are subject-matter of current research. This article reviews recent work on pure and doped He nanodroplets using photoionisation (PI) spectroscopy, an approach which has greatly advanced in the past years. While the notion of the ideal spectroscopic matrix mostly no longer holds in this context, PI techniques provide detailed insights into the photo-physical properties of pure and doped He nanodroplets and their relaxation dynamics following electronic excitation. Exploiting nowadays available high laser fields, even highly ionised states of matter on the nanoscale can be formed. Our particular focus lies on recent experimental progress including femtosecond time-resolved spectroscopy, photoion and electron imaging, and novel sources of highly energetic radiation.